Peran Kinerja Keuangan dalam Memediasi Sustainability Reporting, Good Corporate Governance, dan Ukuran Perusahaan terhadap Nilai Perusahaan pada Perusahaan Sektor Energi - Sulistiani, Cita Ananda; Wahyuningrum, Indah Fajarini Sri (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the influence of sustainability reporting, good corporate governance (GCG), and company size on the value of companies with financial performance as a mediating variable in energy sector companies listed on the Indonesia Stock Exchange. The research approach uses quantitative methods with causality design, as well as secondary data in the form of financial statements and sustainability reports. The research sample consisted of 60 observations obtained through purposive sampling techniques. The analysis was carried out by descriptive statistics, classical assumption tests, multiple linear regression, and mediation tests using the Sobel Test. The results of the study show that sustainability reporting, GCG, and company size have a positive and significant effect on financial performance. Furthermore, financial performance has been proven to have a positive effect on the company's value. In the full model, all independent variables together with financial performance have a significant effect on the company's value. The mediation test confirmed that financial performance partially mediated the relationship between sustainability reporting, GCG, and company size to the company's value. These findings confirm that improving the quality of sustainability reporting, implementing good governance, and optimizing company size can increase company value both directly and through financial performance. The implication of this research is the need for energy sector companies to strengthen transparency, governance, and efficiency of asset management to increase attractiveness in the eyes of investors.